CLINICAL AND ECONOMIC ANALYSIS IN ASSESSMENT OF HEALTH CARE TECHNOLOGIES IN HEALTH CARE INSTITUTIONS - I. B. Gaykovaya; A. T. Burbello; A. I. Ermakov; A. S. Fedorenko; T. V. Vavilova; M. V. Komok (Фармакоэкономика)
the article presents the results of clinical and economic analysis to substantiate the introduction of new methods of clinical and laboratory diagnostics to assess the efficacy of drug therapy of chronic infectious and inflammatory diseases and to evaluate the effectiveness of antiplatelet therapy.